IMPLEMENTATION OF PARKING LEVY MANAGEMENT POLICY IN INCREASING REGIONAL ORIGINAL REVENUE IN MAKASSAR CITY (STUDY ON THE GREATER MAKASSAR PARKING AREA COMPANY) - Putra, Alim Alisa; Sakawati, Herlina; Nur, Andi Cudai (Jurnal Aktor, 2025)
This study aims to find out, analyze and describe how the implementation of the Parking Retribution policy as a source of regional original income in Makassar City. This type of research is descriptive qualitative research with data collection techniques namely observation, interviews, and documentation. The validity of the data is checked by means of source triangulation and technical triangulation. Data analysis techniques use data condensation, data presentation, and drawing conclusions.The results of this study indicate that in order to increase Local Own Revenue through parking fees, it is necessary to make continuous efforts to improve efficiency, transparency, and quality of management of parking fees. Thus, the City of Makassar can optimize the potential revenue from parking fees and strengthen regional finances to support the development and implementation of better public services.